The Effect Of Online Learning On Learning Outcomes Through Independent Learning - Enik Amalia; Ketut Atmaja Johny Artha; Ali Yusuf (Universitas Negeri Padang, 2022)
Online learning that has been carried out at the formal and informal levels is thought to be able to influence student learning outcomes. Learning independence of students is suspected to be one of the predictors that can also affect learning outcomes. This study tries to prove the effect of learning on learning outcomes with or without predictors of the influence of independent learning. This research uses a causal design with path analysis method. 50 out of 180 students of LBB Kumon Waterplace Surabaya were selected to be the research sample using purposive sampling and the formula for 25% of the population. Data analysis using SPSS application with linear regression test. The results of the study showed that online learning with or without intervention from the independent learning of students affected learning outcomes (p < 0.05). The contribution of online learning without an independent learning intervention is 57.9%, while the contribution of online learning with an independent learning intervention is 60.2%. This study proves that there is an effect of online learning with or without independent learning interventions on student learning outcomes.Keywords: Online learning, independent learning, learning outcomes